2020
DOI: 10.3390/ijerph17249435
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Workaholism Research

Abstract: Research on workaholism (also called work addiction by some scholars, especially in the clinical psychology field) has increased substantially in the last few years [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
14
0
3
Order By: Relevance
“…A recent meta-analysis exploring similarities and differences between workaholism and work engagement (Di Stefano & Gaudiino, 2019), concludes that further research on the relationship between the two are required to separate their commonalities and differences. In addition, it has been argued that studies of the interactions between workaholism and other variables have been a neglected area of research (Clark et al, 2016), and a brand-new Special Issue on workaholism advocates for a more complex approach in the research of workaholism and not a singular focus on "main effects" (Balducci, Spagnoli, & Clark, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis exploring similarities and differences between workaholism and work engagement (Di Stefano & Gaudiino, 2019), concludes that further research on the relationship between the two are required to separate their commonalities and differences. In addition, it has been argued that studies of the interactions between workaholism and other variables have been a neglected area of research (Clark et al, 2016), and a brand-new Special Issue on workaholism advocates for a more complex approach in the research of workaholism and not a singular focus on "main effects" (Balducci, Spagnoli, & Clark, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers’ interest in workaholism has grown rapidly in recent years ( Clark et al, 2020 ). Much of the previous research on workaholism (e.g., Taris et al, 2005 ; Bakker et al, 2009 ; Gorgievski et al, 2014 ; Atroszko et al, 2020 ; Dutheil et al, 2020 ) has focused on its negative effects and has suggested that these effects should be prevented as much as possible, as they lead to more disadvantages than advantages for both individuals and organizations ( Balducci et al, 2020 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Furthermore, it has been pointed out that workaholism is positively related to salary increases and promotions in the workplace ( Burke, 2001 ). It has also been highlighted that the globalized competitive environment in which modern companies operate affirms long working hours and reinforces workaholic behavior ( Balducci et al, 2020 ). Based on these findings, it is undeniable that some aspects of workaholic behavior are easily affirmed in many companies.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Several researches provide robust evidence that workaholism is an addiction to work that leads to many negative individual, interpersonal, and organizational outcomes (Clark et al 2016), and is characterized by working excessively (Schaufeli et al 2008). According to Balducci et al (2020a), there is a certain consensus regarding the definition of workaholism: being obsessed with work, a significant psychological dysfunction characterized by an excessive concern with work, and an uncontrollable internal desire to invest too much in work activities.…”
Section: Introductionmentioning
confidence: 99%
“…This happens because working from home is ingrained into family life, which affects relationships, as well as physical and mental health. Globalized competition, characteristic of modern societies, contributes to perpetuating workaholic behavior, which is reflected in a long workday, reinforced by tangible (e.g., promotion) and intangible (e.g., compliment) rewards (Balducci et al 2020a). Thus, workplace spirituality can be a key factor; it is a multidimensional construct and a positive means to improve the success and competitiveness of organizations, as well as employees' well-being.…”
Section: Introductionmentioning
confidence: 99%